Implementation of adjustive latency compensation in a binaural hearing aid to prevent latency due to wireless transmission for using with multi-media devices. (2015) - Wei, Qun; Seong, Ki Woong; Lee, Jyung Hyun; Park, Hee-Joon; Kim, Myoung Nam; Cho, Jin-Ho
Binaural hearing aid has become an important topic in recent research on hearing aids. It employs two hearing aids, one for each ear. However, a short latency between the outputs of the two hearing aids will occur owing to the wireless data transmission between two aids. In this study, an adjustive latency compensation was designed and implemented in a binaural hearing aids to prevent the latency. It includes a static part for the basic transmission time, and the length of an adjustive part can be adjusted depending on the transmission time change caused by a transmission failed. Therefore, a time measurement program with real time clock was designed to measure the time of every data package transmission. As the experimental results show, the proposed compensation is able to ensure synchronisation between the two hearing aids even when a transient failure in the wireless communication between two hearing aids occurred.